Stories from below: Human remains at the Gothenburg Museum of Natural History and the Museum of World Culture - Lindskoug, Henrik Bernhard (2015)
This article adopts a 'cultural biography' approach to the examination of an archaeological collection from Arica, Chile, involving two museums located in Gothenburg, Sweden. It provides a comprehensive overview of the history of the collection and how the meanings and contexts of a cranium belonging to this collection have changed over time. Different stages in the biography of the cranium are reconstructed here: we document and describe a shift within the western museum world, focusing on Sweden, from considering the scientific value of human remains to considering another dimension linked to livelihood and personhood; we claim that following the intimate trajectory of an object permits us to move through and document the changing value systems in the history of museums in Sweden and its links to the early development of archaeology in South America, together with the collecting practices of Swedish and German scholars such as Max Uhle and Erland Nordenskiöld.